A precisely dated climate record for the last 9 kyr from three high alpine stalagmites, Spannagel Cave, Austria - Aeschbach, Nicole; Scholz, Denis; Mühlinghaus, Christian; Mangini, Augusto; Spötl, Christoph (Geophysical research letters, 2006)
Here we use the δ18O time-series of three stalagmites from the high alpine Spannagel cave (Austria) which grew in small distance from each other to construct a precisely dated, continuous δ18O curve for the last 9 kyr (COMNISPA). This speleothem record is not influenced by effects of kinetic isotope fractionation due to the low temperatures in the cave. Thus, the variations in δ18O can be interpreted in terms of past climate change. COMNISPA exhibits several oscillations within the Holocene, and their timing and duration is in agreement with that documented by other alpine archives.
Online veröffentlicht: 24. Oktober 2006
Gesehen am 22.12.2025